2019
DOI: 10.1101/567206
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Major QTLs for resistance to early and late leaf spot diseases are identified on chromosomes 3 and 5 in peanut (Arachis hypogaea)

Abstract: Early and late leaf spots are the major foliar diseases of peanut responsible for severely decreased yield in the absence of intensive fungicide spray programs. Pyramiding host resistance to leaf spots in elite cultivars is a sustainable solution to mitigate the diseases. In order to determine the genetic control of leaf spot disease resistance in peanut, a recombinant inbred line population (Florida-07 x GP-NC WS16) segregating for resistance to both diseases was used to construct a SNP-based linkage map cons… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 52 publications
(30 reference statements)
1
17
0
Order By: Relevance
“…ELS and LLS are major diseases of peanuts and the range of severity is strongly influenced by G x E associated with many QTLs [21][22][23]. Only a few peanut genotypes have been identified as medium tolerant to leaf spot diseases and specific crosses were generated to develop more tolerant lines [8]. Marker types, such as simple sequence repeats (SSRs) and Insertions/Deletions (Indels), were applied to select leaf spot resistant lines [24,25], but validation has been difficult due to variations in leaf spot disease phenotyping (strong environmental effect, different levels of pathogen pressure, state of plant health).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ELS and LLS are major diseases of peanuts and the range of severity is strongly influenced by G x E associated with many QTLs [21][22][23]. Only a few peanut genotypes have been identified as medium tolerant to leaf spot diseases and specific crosses were generated to develop more tolerant lines [8]. Marker types, such as simple sequence repeats (SSRs) and Insertions/Deletions (Indels), were applied to select leaf spot resistant lines [24,25], but validation has been difficult due to variations in leaf spot disease phenotyping (strong environmental effect, different levels of pathogen pressure, state of plant health).…”
Section: Discussionmentioning
confidence: 99%
“…Identification of major genes for disease resistance has been very elusive based on strong environmental and genetic interactions and the involvement of multiple QTLs [7][8][9]. The nature of plant and fungal interactions makes visual selections highly variable based on years and locations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, seven and four STAs identified in NAM‐T and NAM‐F, respectively, co‐located in QTL regions of PW and SW in both seasons on chromosomes A05. Chu et al () identified a QTL on B05 overlaps for pod yield and LLS resistance. Interestingly, in this study we also reported QTLs for both PW and SW in both NAM populations on B05.…”
Section: Discussionmentioning
confidence: 99%
“…The primary objective of this developed genetic resource was to share these populations with the peanut research community and to undertake high‐resolution phenotyping of these populations (Chu et al , ; Holbrook et al , ). The parents represent a wide range of agronomic, morphological and disease resistance traits, and some biparental populations have been studied for resistance to early and late leaf spot diseases (Chu et al , ; Clevenger et al , ). These two NAM populations thus could combine the strengths of both linkage and association mapping since the NAM populations have higher power QTL detection as compared with biparental mapping populations (Guo et al , ; Wang et al , ; Yu et al , ).…”
Section: Introductionmentioning
confidence: 99%